The Role of Teacher Strategies in Increasing Student Motivation in Aqidah Akhlak Subjects - Asriani, Asriani; Halik, Abdul; Buhaera, Buhaera; Marhani, Marhani; Nurhayati, St (International Journal of Business, Law, and Education, 2024)
A concise and factual abstract is required. The abstract should state This study aims to determine student learning motivation, teacher strategies, and supporting and inhibiting factors in increasing Aqidah Akhlak’s learning motivation. The descriptive qualitative approach is research that describes stimuli and events factually and systematically regarding the factors, characteristics, and relationships between phenomena owned to do the basics only. The research uses a credibility or trust test to assess the results. The main findings of this study show that students’ Aqidah Akhlak learning motivation can be increased by applying various creative learning methods, appropriate reward strategies, and adjustments to student needs. Supporting factors include student enthusiasm, teacher competence, learning facilities, a conducive environment, positive friends, and family support. Meanwhile, the inhibiting factors include unsupportive family conditions, less than optimal student and teacher health, a less conducive classroom environment, and negative peer influence.